Caveat Compounder: A Warning about Using the Daily CRSP Equal-Weighted Index to Compute Long-Run Excess Returns - Canina, Linda; Michaely, Roni; Thaler, Richard; Womack, Kent (Journal of Finance, 1998)
This paper issues a warning that compounding daily returns of the Center for Research in Security Prices (CRSP) equal-weighted index can lead to surprisingly large biases. The differences between the monthly returns compounded from the daily tapes and the monthly CRSP equal-weighted indices is almost 0.43 percent per month, or 6 percent per year. This difference amounts to one-third of the average monthly return, and is large enough to reverse the conclusions of a paper using the daily tape to compute the return on the benchmark portfolio. We also investigate the sources of these biases and suggest several alternative strategies to avoid them.